BIMBINGAN TEKNIS ANALISIS PENENTUAN HARGA JUAL BUSANA MUSLIM DAN MUSLIMAH PADA USAHA CITRA GALLERY DI KELURAHAN KAMBU KOTA KENDARI - Teguh Permana; Andriani Puspitaningsih; Elsih Fitriani Arif (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
This service activity aims to increase the understanding of business owners about determining the right price so that managers can increase their business turnover and managers can innovate and deal with working capital turnover. The method used is a lecture on business management, which consists of funding and working model turnover, and business innovation. Then guidance on determining the selling price. The results of this service show that the target audience can accept what the service team conveys. Business owners can also easily understand variable costs, fixed costs, direct and indirect cost components so that business owners can easily decide at what price to sell their merchandise in order to get a big profit. However, for the BEP method, the manager finds it difficult because it is considered complicated because so far the owner has determined prices based on available stock and standard prices between competitors. With this guidance, business owners find it helpful because so far in determining prices, they are only based on the owner's estimates.